The occurrence of high-risk factors for hearing loss in verylow- birth-weight neonates: A retrospective exploratory study of targeted hearing screening - Amisha Kanji; Katijah Khoza-Shangase (South African Journal of Communication Disorders, 2012)
The current study aimed at determining the type and frequency of high-risk factors for hearing loss in a group of very-low-birth-weight (VLBW) neonates in a tertiary hospital in South Africa with the objective of collating evidence that could be used in arguing for or against revisiting targeted hearing screening in developing countries. Furthermore, the study aimed at investigating the relationship between the identified high-risk factors and hearing screening results. In a retrospective data review design, data were collated from files from the VLBW project; this included hearing screening records, as well as records from participant medical and audiology files. Records of 86 neonates with birth weights ranging between 680 g and 1 500 g were reviewed. Findings indicated that neonatal jaundice, exposure to human immunodeficiency virus (HIV), mechanical or assisted ventilation, and neonatal intensive care unit stay greater than 48 hours were the most frequently occurring high-risk factors for hearing loss in the current sample. These factors are consistent with those listed in the high-risk register of the Health Professions Council of South Africa for the South African context. Findings confirm the complexity of risk factors, and the influence that a variety of factors such as poor follow-up or return rate might have on the implementation of early hearing detection and intervention. The importance of establishing context-specific risk factors for effective implementation of targeted screening protocols where universal newborn hearing screening is not yet a reality was highlighted by the current study.